2019
DOI: 10.1186/s12891-019-2744-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of tibial torsion on tibial osteotomy in knee arthroplasty using a three-dimensional computed tomography-based modelling technique

Abstract: Background Extramedullary systems are commonly used in knee arthroplasty, with the rod location being determined from the tibial torsion line during surgery. The traditional method for tibial torsion measurement is not in accordance with clinical practice. This study aimed to evaluate proximal and distal tibial torsion using 3-dimensional (3D) computed technology to establish a new evaluation method, as well as to investigate the association between tibial torsion and postoperative alignment devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This optimizes load distribution during the mono‐ and bipedal phases of gait [10, 16] and is supposed to permit a more "natural feeling" [23]. Among the current alignment concepts, JL parallelism is most likely achieved with KA [9, 10, 15, 16]. Thus, it might be assumed that patients with KA TKA are more satisfied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This optimizes load distribution during the mono‐ and bipedal phases of gait [10, 16] and is supposed to permit a more "natural feeling" [23]. Among the current alignment concepts, JL parallelism is most likely achieved with KA [9, 10, 15, 16]. Thus, it might be assumed that patients with KA TKA are more satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…To “forget” about an artificial joint, because it feels natural can be considered the ultimate goal of arthroplasty. PRO assessed with the FJS‐12 seem to favor KA TKA compared to MA TKA [14–17] with an average of 46–80 points at mid‐term follow‐up. Compared with the literature [21–23], the mean FJS‐12 in our series was even slightly better, exceeding the mean normative values for FJS‐12 reported for the given age group (68 points in women and 79 points in men [12]).…”
Section: Discussionmentioning
confidence: 99%
“…17 A most recent study indicated that the condylar volume and superficial area of the scissors-bite side were significantly greater than those on the non-scissors-bite side in patients with unilateral scissors-bite. 18 Nonetheless, these studies include individuals who have at least one posterior tooth with scissors-bite rather than patients with unilateral Brodie bite. Moreover, the condylar position is rarely investigated three-dimensionally in patients with unilateral Brodie bite.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, it was found that the mandibular body and condylar process were remarkably asymmetrical in patients with unilateral scissors bite by the “surface‐to‐surface” mapping method 17 . A most recent study indicated that the condylar volume and superficial area of the scissors‐bite side were significantly greater than those on the non‐scissors‐bite side in patients with unilateral scissors‐bite 18 . Nonetheless, these studies include individuals who have at least one posterior tooth with scissors‐bite rather than patients with unilateral Brodie bite.…”
Section: Introductionmentioning
confidence: 99%